Effect of Vitamin D in HN9.10e Embryonic Hippocampal Cells and in Hippocampus from MPTP-Induced Parkinson’s Disease Mouse Model - Cataldi, Samuela; Arcuri, Cataldo; Hunot, Stéphane; Mecca, Carmen; Codini, Michela; Laurenti, Maria E.; Ferri, Ivana; Loreti, Elisabetta; Garcia-Gil, Mercedes; Traina, Giovanna; Conte, Carmela; Ambesi-Impiombato, Francesco S.; et al. (Frontiers in Cellular Neuroscience, 2018)
It has long been proven that neurogenesis continues in the adult brains of mammals in the dentatus gyrus of the hippocampus due to the presence of neural stem cells. Although a large number of studies have been carried out to highlight the localization of vitamin D receptor in hippocampus, the expression of vitamin D receptor in neurogenic dentatus gyrus of hippocampus in Parkinson’s Disease (PD) and the molecular mechanisms triggered by vitamin D underlying the production of differentiated neurons from embryonic cells remain unknown. Thus, we performed a preclinical in vivo study by inducing PD in mice with MPTP and showed a reduction of glial fibrillary acidic protein (GFAP) and vitamin D receptor in the dentatus gyrus of hippocampus. Then, we performed an in vitro study by inducing embryonic hippocampal cell differentiation with vitamin D. Interestingly, vitamin D stimulates the expression of its receptor. Vitamin D receptor is a transcription factor that probably is responsible for the upregulation of microtubule associated protein 2 and neurofilament heavy polypeptide genes. The latter increases heavy neurofilament protein expression, essential for neurofilament growth. Notably N-cadherin, implicated in activity for dendritic outgrowth, is upregulated by vitamin D.